Law Enforcement Against the Crime of Trading in Protected Animals (Case Study Decision Number: 3295/Pid.B/Lh/2019/Pn.Sby) - Sarda Novanda; Emy Rosnawati (Indonesian Journal of Law and Economics Review, 2021)
The purpose of this study is to analyze law enforcement practices on the criminal acts of protected wildlife trade and analyze legal considerations by judges on Decision No. 3295/Pid.B/LH/2019/PN. Sby. The results show that law enforcement practices on the criminal act of trafficking protected animals is referring to Law No. 5 of 1990 on Conservation of Biological Natural Resources and Ecosystems. The results also showed that the legal consideration by the judge on The Verdict Number: 3295/Pid.B/LH/2019/PN. Sby has considered sociological, philosophical and juridical considerations so that the granting of imprisonment for 1 (one) year and a fine of Rp 25,000,000 (twenty-five million rupiah) provided that if the fine is not paid will be replaced with a fine of 1 (one) month in prison is considered appropriate and effective.